Sustainable exploitation of biological populations - Grasman, Joran (Zielona Góra: Uniwersytet Zielonogórski)
For a system of nonlinear difference equations that models the dynamics of exploited biological populations, a locally optimal periodic solution is constructed. If this solution is unstable, a stabilizing feedback in the harvesting is introduced. The method is applied to an age-structured population model in fishery as well as to a host-parasitoid system for which the number of hosts and the number of introduced parasitoids should be minimized.
Keywords: optimal harvesting; system of nonlinear difference equations; fishery; host-parasitoid system; stabilizing feedback